Penerapan Relaksasi Otot Progresif Terhadap Penurunan Tekanan Darah Pada Lansia Dengan Hipertensi - Iqbal Fanani; Norman Wijaya Gati (Lembaga Pengembangan Kinerja Dosen, 2024)
Background: The elderly are said to have a risk of developing various degenerative diseases, one of which is hypertension. According to data from the World Health Organization (WHO) in 2023 the prevalence of 1.28 billion people with hypertension aged 30-79 years. The prevalence of hypertension at Sibela Health Center in 2022 was 12,447 hypertensive patients with the highest incidence rate in Surakarta City, One of the non-pharmacological therapies that can be given to elderly hypertensive patients is progressive muscle relaxation. Objective: Describe the results of blood pressure comparison before and after the application of Progressive Muscle Relaxation in the elderly. Method: This study used a descriptive research design with a case study approach by observing blood pressure in 2 elderly respondents, carried out 2x a day for 3 consecutive days within 15 minutes. The instruments used were observation sheets, Blood Pressure Monitors, and stopwatches. Results: There is a decrease in blood pressure after giving Progressive Muscle Relaxation to Mrs. D from grade 1 hypertension to normal and in Mrs. S from grade 2 hypertension to grade 1 hypertension. Conclusion: The application of progressive muscle relaxation therapy can potentially reduce blood pressure in the elderly with hypertension in both respondents.